Microscope-Integrated Intraoperative Optical Coherence Tomography–Guided Big-Bubble Deep Anterior Lamellar Keratoplasty. Issue 1 (January 2022) - Santorum, Paolo; Yu, Angeli Christy; Bertelli, Enrico; Busin, Massimo
Abstract : Purpose: The purpose of this study was to evaluate the feasibility of microscope-integrated intraoperative optical coherence tomography (OCT) for real-time quantitative analysis of surgical planes in big-bubble deep anterior lamellar keratoplasty (DALK). Methods: In this interventional case series, intraoperative OCT-guided big-bubble DALK was performed in 16 consecutive eyes of 16 patients with keratoconus. Trephination depth was measured using the intraoperative OCT caliper tool. Aiming for a depth within 150 μm from the endothelial surface, the trephination groove was extended to a deeper plane using a 15-degree blade. Repeat OCT scans were taken to measure residual stromal thickness before insertion of the DALK probe from the bottom of the extended trephination. Caliper measurements, success rate of pneumatic dissection, and complications were recorded. Results: After trephination, residual stromal thickness exceeded 150 μm in all eyes and averaged 257.1 ± 42.5 μm. In each case, the initial trephination groove was extended to a depth within 150 μm from the endothelial surface (118.9 ± 27.1 μm). Big-bubble formation was achieved in 12 eyes (75%). Type 1 bubble was obtained in 11 eyes. Perforation requiring conversion to penetrating keratoplasty occurred in 4 eyes during insertion of the cannula into a residual stromal bed of <100 μm (n = 2; 63 and 75 μm) or layer-by-layer dissection (n = 2). Conclusions: Quantitative analysis of intraoperative OCT scans can be used to assist decision-making on whether to proceed with pneumatic dissection or extend the trephination groove, thereby facilitating insertion of the injection cannula at the desired stromal depth. Abstract : Supplemental Digital Content is Available in the Text.